On uniqueness of a classical solution of the system of non-linear 1-D Saint Venant equations - Lai, Hoang Van; Long, Le Mau; Chung, Mai Dinh (Vietnam Journal of Mechanics, 1999)
In this paper the theorem of uniqueness of a classical solution of the system of non-linear 1-D Saint Venant equations is proved. This uniqueness theorem is setup for the system of non-linear 1-D Saint Venant equations in canonical form under respective initial and boundary conditions.